2019
DOI: 10.15666/aeer/1702_33433351
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foliar Sodium Selenate on Leaf Senescence of Fragrant Rice in South China

Abstract: Selenium (Se) is an essential element to humans, animals and plants, but little is known about roles of Se in yield and antioxidant enzyme activities of rice. In this study, sodium selenate with 10 (T1), 30 (T2) and 50 (T3) μmol L -1 concentrations and distilled water (CK) were sprayed onto rice cultivars, or more precisely Meixiangzhan-2 at rupturing stage during the experiments in South China, 2017. Treatments were arranged in a split-plot design with three replications. The result showed that spraying 10, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
3
6
0
Order By: Relevance
“…Our results agreed with the study of Duan et al. (2019), who indicated that application of the appropriate amount of Se increased rice yield by delaying leaf senescence and enhancing photosynthesis. A similar discovery was reported by He et al.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results agreed with the study of Duan et al. (2019), who indicated that application of the appropriate amount of Se increased rice yield by delaying leaf senescence and enhancing photosynthesis. A similar discovery was reported by He et al.…”
Section: Discussionsupporting
confidence: 93%
“…An early study has evidenced that the application of Se at heading stage improved grain yield of rice by enhancing the photosynthesis during the grain-filling stage (Lai et al, 2019). Our results agreed with the study of Duan et al (2019), who indicated that application of the appropri-ate amount of Se increased rice yield by delaying leaf senescence and enhancing photosynthesis. A similar discovery was reported by , who demonstrated that foliar application of selenite at low concentration could enhance antioxidant enzymes activities and chlorophyll biosynthesis to ensure the goal of higher yield.…”
Section: Discussionsupporting
confidence: 91%
“…Chlorophyll concentration is an important factor in affecting fragrant rice photosynthesis which is a key bioprocess for yield formation [12]. A previous study showed that agronomy measures such as water management and microelement were used to increase chlorophyll concentrations and photosynthesis so the goal of higher grain yield would be achieved in fragrant rice production [13,14]. In our study, BR had similar positive effects on the yield formation of fragrant rice and the possible reason might be exogenous BR enhancing biosynthesis of chlorophyll.…”
Section: Discussionsupporting
confidence: 69%
“…The microclimate and environment of the paddy field are very complex, sometimes it will cause stress (transient extreme temperature, pest, water stress) to the growing rice and induce oxidative damage and membrane peroxidation which could be judged by MDA concentration [14][15][16][17]. As the key enzymes on cleaning reactive oxygen, GPX, SOD and CAT play important roles in an antioxidant system in fragrant rice [18].…”
Section: Discussionmentioning
confidence: 99%
“…In plants, moderate Se is not considered essential but acts as a clearly beneficial element and can promote plant growth (Pilon-Smits et al, 2017;Jia et al, 2018). It has been shown to be involved in the regulation of photosynthesis and respiration, stress resistance, antioxidant capacity, abiotic stress tolerance, and alleviation of heavy metal stresses (Ulhassan et al, 2019;Dai et al, 2019;Duan et al, 2019). It is important to point out that there is a narrow range of Se accumulation in tissues within which Se deficiency transitions to toxicity in humans, animals, and plants.…”
Section: Introductionmentioning
confidence: 99%